2005
DOI: 10.1177/0892705705043535
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Thermoplastic Polyester Preform Binder on Vinyl Ester Resin

Abstract: This study characterizes and evaluates the effects of a thermoplastic polyester preform binder on a thermosetting vinyl ester resin. It was observed that the binder material is soluble in the resin and that the dissolution of the binder drastically affects the viscosity of the resin. It was determined that the binder can significantly delay the gel time, and influence the reaction kinetics of the resin. Additionally, results show that the binder concentration and extent of dissolution affect the mechanical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Hence, the polyester does not exhibit a melting endotherm. The thermophysical properties and DSC thermogram of the thermoplastic polyester are almost identical to those of the binder used by Tanoglu et al [10,12,13] and Brody and Gillespie [11,14], again indicating that the commercial binder systems are similar to poly(4,4 0 -dipropoxy-2,2 0 -diphenyl propane fumarate). …”
Section: Thermoplastic Polyester Thermal Propertiessupporting
confidence: 54%
See 1 more Smart Citation
“…Hence, the polyester does not exhibit a melting endotherm. The thermophysical properties and DSC thermogram of the thermoplastic polyester are almost identical to those of the binder used by Tanoglu et al [10,12,13] and Brody and Gillespie [11,14], again indicating that the commercial binder systems are similar to poly(4,4 0 -dipropoxy-2,2 0 -diphenyl propane fumarate). …”
Section: Thermoplastic Polyester Thermal Propertiessupporting
confidence: 54%
“…They suggested that a hindered bonding between glass fibres and matrix resin due to coverage of the fibre surfaces by the binder resulted in this decrease in interlaminar fracture toughness. Brody and Gillespie also studied the effect of a ATLAC 363E thermoplastic polyester binder on the mechanical properties of vinyl ester resin [14] and glass/vinyl ester composite laminates [11]. Single Edge Notched Beam (SENB) tests indicated that the fracture toughness of the vinyl ester resin was not affected by presence of the binder.…”
Section: Introductionmentioning
confidence: 96%
“…It has been confirmed that the material properties of both textile preforms and matrix are influenced due to the application of preforming binder or tackifier [40][41][42][43][44][45][46][47][48][49]. For instance, the fiber wetting would be affected by lowered capillary pressure when the interstitial gaps within the fiber tows were blocked by the preforming binder [48].…”
Section: Introductionmentioning
confidence: 71%
“…For instance, the fiber wetting would be affected by lowered capillary pressure when the interstitial gaps within the fiber tows were blocked by the preforming binder [48]. Furthermore, the dissolution of the preforming binder can drastically affect the viscosity, the gel time and the reaction kinetics of the resin [43,45]. In the serial investigations the authors have studied the influence of the preforming binder on the compaction behavior of the textile preforms [42] and the thermal and rheological properties of the catalyzed CBT oligomers.…”
Section: Introductionmentioning
confidence: 98%
“…It results from the thread displacement and falling apart the textile structure during formation [17,18]. In order to avoid these problems, structure fixing over the entire surface is being analyzed [19][20][21][22][23]. It is a good solution for the preforms with a low deformation degree.…”
Section: Introductionmentioning
confidence: 99%